Ekonomiczne aspekty ograniczania bezrobocia w polskim rolnictwie - Kociszewska, Irena; Szydło, Wiktor (Economic Aspects of Unemployment Reduction in Rural Areas in Poland, 2005)
The article deals with some aspects of unemployment in Polish agriculture. The official data underestimate the problem. There is no consistent policy aimed at increasing employment rate in the rural areas. New EU programs are not popular among farmers while changes in the farmer's social insurance additionally worsen the situation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 443-449